(untitled) (Chittagong University Journal of Biological Sciences, 2024)
This paper presents the impacts of flash floods on women’s life with a gender view which has been conducted on Fatikchhari Upazila under Chittagong District. The Halda River is mainly responsible for flash flood in this area. The study was aimed to know the causes of flash floods and to investigate the impact on women life and livelihoods. The semi structured questionnaire survey for primary data collection and physical observation method was followed to fulfill the goals. 25-50 years aged women were selected as target group for survey as this group solely has been facing the household damages with the flood water. Therefore, women suffered more than men in terms of resource and emotional trauma. The result showed that most of the women claimed excess rainfall for flash flood and loss of agricultural production by flooding agricultural land. In the study area due to poor income, insufficient shelter, poor building materials, water and sanitation, lack of education, physical strength, child protection, health care facilities, religious cause, awareness, self-causes women are more affected than man. Moreover, women’s limited access to resources and decision making process increase their vulnerabilities. To solve these problems integration of gender, women issues into disaster research, planning, and organizational practice is needed for development. The Chittagong Univ. J. B. Sci.,Vol. 10(1 &2):41-51, 2020.